2004
DOI: 10.1007/s10236-004-0093-8
|View full text |Cite
|
Sign up to set email alerts
|

Sea-level oscillations with 6-h period in the North Sea 29?31 October 2000. An analysis of data from stations in the northern North Sea and along the western coast of Norway

Abstract: During the storm event 29-31 October 2000 long regular trains of residual sea-level oscillations with period about 6 h occurred in the North Sea area. Crestto-trough heights up to 0.8 m were observed along the western coast of Norway. Model simulations show that these oscillations were mainly due to spatial and temporal variations in the atmospheric forcing and were not the result of nonlinear tide-surge interaction. The oscillations propagated northwards along the Norwegian coast and the signal was amplified … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
2
0
1

Year Published

2009
2009
2013
2013

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 12 publications
1
2
0
1
Order By: Relevance
“…The modelled volume flux through the strait of Drøbaksundet in Oslo indicated that the velocity could have been 5 m/s. Other similar effects were reported in [54], where the amplitude of a sea level oscillation was 0.8 m along the west coast of Norway, triggered by spatial and temporal variations in the atmospheric forcing during a storm event.…”
Section: Tidessupporting
confidence: 53%
See 2 more Smart Citations
“…The modelled volume flux through the strait of Drøbaksundet in Oslo indicated that the velocity could have been 5 m/s. Other similar effects were reported in [54], where the amplitude of a sea level oscillation was 0.8 m along the west coast of Norway, triggered by spatial and temporal variations in the atmospheric forcing during a storm event.…”
Section: Tidessupporting
confidence: 53%
“…For completeness it should be mentioned that Gjevik and his co-workers also modelled tidal flow and/or effects, sometimes in combination with weather changes, in the Oslo Fjord [53], the Barents Sea [68], and the North Sea [54]. It appears the models used for these papers were earlier versions of the model described above.…”
Section: The University Of Oslo Modelmentioning
confidence: 99%
See 1 more Smart Citation
“…Dabar tinkle veikia apie 200 vandens lygio stebėjimo stočių, matuojančių jūros lygio pokyčius arba teikiančių susijusią informaciją iš kitų šaltinių -altimetrinių ir GPS palydovų, absoliučiojo sunkio pagreičio matavimo punktų, meteorologinių daviklių ir pan. Tokie kompleksiniai stebėjimai svarbūs hidrologijoje, meteorologijoje, navigacijoje, jūrų geodezijoje ir kitose mokslo bei praktinės veiklos srityse [10][11][12][13][14][15][16]. #!/usr/bin/perl use POSIX qw(setsid); system "stty -F /dev/ttyS0 parenb cs7 9600"; system "echo \"r\" > /dev/ttyS0"; open (COM1,"</dev/ttyS0");…”
Section: Koordinuoti Ir Kur Būtina Inicijuoti Jūros Lygiounclassified